Moses in Corinth : the apologetic context of 2 Corinthians 3 - Duff, Paul B., 1952- (Novum Testamentum, Supplements, 2015)
Scholars have long puzzled over the imagery focused on Moses in 2 Corinthians 3; it is unclear how that imagery fits into the larger context of the letter. Many have explained the imagery as the apostle's reaction to the "super-apostles," Jewish missionaries mentioned later in the letter. These preachers, it has been argued, promoted either a θεῖος ἀνήρ or a Judaizing agenda. In Moses in Corinth , Paul B. Duff contends that the Moses imagery has nothing to do with the super-apostles but functions instead as an integral part of Paul's first apologia sent to Corinth. This apologia , found in 2 Cor 2:14-7:4, represents an independent letter sent to dispel suspicions about the apostle's honesty, integrity, and poor physical appearance.